DIFFICULTIES FACED BY THE STUDENTS IN ANSWERING TOEFL TEST QUESTIONS - Nurfitriyah Halim; Sri Yulianti Ardiningtyas (Universitas Islam Negeri Alauddin Makassar, 2018)
This research was aimed at identifying the difficulties in answering TOEFL test questions. This research applied a focused description as the method of collecting the data and was located within a qualitative research paradigm. The population of the research was the seventh-semester students of English Department of STKIP YPUP who have undertaken TOEFL test for any purposes, and the sample of this research was chosen by using homogenous sampling. The sample consisted of 30 students. The data is collected using an open-ended questionnaire. The order of data collecting was listing the target population, selecting the sample subject, distributing a questionnaire and collecting the questionnaire. Concerning this research, it was focused in finding out the difficulties faced by the students in answering TOEFL test questions. The difficulties are personal trait based on their experience. This research was restricted to the difficulties in answering TOEFL test of English department students at the seventh-semester in STKIP YPUP Makassar who have undertaken TOEFL test for any purposes before. The findings of this research was the difficulties faced by the students in answering the TOEFL test questions, they were, fewer basic skills, less practice, less motivation, and students’ individual differences.